Functional composition of initial soil fungi explains the difference in mass loss of Phragmites australis litter in different habitat conditions across multiple coastal wetlands - Ping, Yunmei; Pan, Xu; Cui, Lijuan; Li, Wei; Hu, Yukun; Cornelissen, Johannes H. C. (Frontiers in Environmental Science, 2024)
The differences in mass loss of leaf litter are primarily thought to be driven by microbial activity, especially by fungi. However, the existence of such differences across large spatial scales has not been well explored in field studies and the underlying mechanisms of difference are still unclear, especially for the role of different fungal guilds in driving different mass losses. we conducted a one-year decomposition study within each of four coastal wetlands in China to test the difference in mass loss across a large spatial scale (ranging from 26° N to 41° N in latitude). In each wetland, six sites including three composed of Phragmites australis and three composed of another dominant plant species typically in coastal ecosystems were selected. We used P. australis leaf litter as the standard decomposition material, placing it into litter bags with mesh sizes 1 mm and 4 mm, respectively. Final litter mass loss was examined approximately after 3, 9 and 12 months. The different mass loss was quantified using additional mass loss at P. australis sites compared to that at another species sites. We found that the mass loss of leaf litter of P. australis showed a clear difference across multiple coastal wetlands only at later stages of decomposition, which was independent of mesofauna (mesh size) contribution to decomposition. Furthermore, the observed difference in mass loss was primarily attributed to the dissimilarities in initial soil fungal community, particularly the symbiotrophic fungi, rather than the soil bacterial community. Our results provide empirical evidence of a large-scale difference in mass loss in litter decomposition and have linked the observed difference to different soil fungal guilds. These results indicate that symbiotrophic fungi might play a direct or indirect role in driving difference in mass loss, which contributes to a better understanding and invites in-depth further investigation on the underlying microbe-driven mechanisms of the difference.